Moderating effect of self-efficacy in the relationship between knowledge, attitude and environment behavior of cybersecurity awareness - Che Zainal, Norhafizah; Mohd Puad, Mohd Hazwan; Mohd Sani, Nor Fazlida (Canadian Center of Science and Education, 2021)
Today, cybersecurity is a growing issue in our education society to ensure a safe teaching and learning process for teachers and students. Reports and studies demonstrated that teachers and students are moderately aware of the cybersecurity threat surrounding them that could affect the learning curve and other fatal impacts. This study aims to identify the role of self-efficacy in the relationship between knowledge, attitude, and environment behavior of cybersecurity awareness. The researchers used a correlational design with a quantitative approach by using a questionnaire instrument to collect data from teacher respondents. A total of 350 teachers in took part in this survey voluntarily, distributed using social media applications in the midst of the Covid-19 pandemic. The researchers used the IBM SPSS Statistics to analyze the data descriptively and inferentially. The levels of knowledge, attitude, self-efficacy, and environment behavior of Malaysian school teachers towards cybersecurity awareness are low. Self-efficacy acts as a moderator in influencing the relationship between knowledge, attitude, and environment behavior of cybersecurity awareness. Strategies and programs need to be initiated by stakeholders to increase the self-efficacy of cybersecurity that could assist the positive change of environment behavior among teachers for teaching and learning benefit.